Learn more about

Refine search

Results (displaying matches 1-50 of 78) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
10800.c.691200.1 10800.c \(y^2 + (x^3 + x)y = x^6 - 22x^4 - 37x^2 - 15\) $G_{3,3}$ 0
12909.b.12909.1 12909.b \(y^2 + (x^3 + 1)y = -x^6 + 15x^5 - 86x^4 + 105x^3 + 4x^2 - 27x - 6\) $\mathrm{USp}(4)$ 0
13108.a.26216.1 13108.a \(y^2 + (x^2 + x)y = x^5 - 59x^4 - 21x^3 + 106x^2 + 5x - 63\) $\mathrm{USp}(4)$ 0
15680.b.250880.1 15680.b \(y^2 + (x^2 + 1)y = -112x^6 + 93x^4 - 2x^2 - 9\) $G_{3,3}$ 0
16281.a.48843.1 16281.a \(y^2 + (x^2 + 1)y = x^5 - 101x^4 + 9x^3 + 105x^2 - 5x - 28\) $\mathrm{USp}(4)$ 0
32820.a.65640.1 32820.a \(y^2 + (x^2 + x)y = -7x^6 - 5x^5 + 54x^4 + 59x^3 - 58x^2 - 64x - 14\) $\mathrm{USp}(4)$ 0
36356.b.72712.1 36356.b \(y^2 + (x^2 + x)y = -3x^6 - 13x^5 + 11x^4 + 53x^3 - 37x^2 + 28x - 65\) $\mathrm{USp}(4)$ 0
37375.b.37375.1 37375.b \(y^2 + (x^3 + x)y = -x^6 - x^5 + 21x^4 + 26x^3 - 155x^2 - 166x + 3\) $\mathrm{USp}(4)$ 0
38267.a.38267.1 38267.a \(y^2 + xy = 18x^6 - 35x^5 + 55x^4 - 54x^3 + 34x^2 - 17x + 2\) $\mathrm{USp}(4)$ 0
65563.d.65563.1 65563.d \(y^2 + x^2y = x^5 - 224x^4 - 352x^3 - 198x^2 - 47x - 4\) $\mathrm{USp}(4)$ 0
65563.d.65563.2 65563.d \(y^2 + xy = x^5 + 32x^4 + 262x^3 + 32x^2 + x\) $\mathrm{USp}(4)$ 0
72000.b.72000.1 72000.b \(y^2 + (x^3 + x)y = -x^6 - 7x^4 + 21x^2 - 15\) $G_{3,3}$ 0
74900.a.749000.1 74900.a \(y^2 + (x^2 + x)y = 2x^5 - 61x^4 - 93x^3 + 195x^2 + 155x - 220\) $\mathrm{USp}(4)$ 0
80730.a.242190.1 80730.a \(y^2 + (x^2 + x)y = 22x^6 + 7x^5 + 61x^4 + 14x^3 + 61x^2 + 7x + 22\) $G_{3,3}$ 0
102016.b.102016.1 102016.b \(y^2 + xy = -x^6 - 8x^5 - 8x^4 + 32x^3 - 16x^2 + x - 1\) $\mathrm{USp}(4)$ 0
106015.b.742105.1 106015.b \(y^2 + (x^2 + x)y = 7x^5 - 66x^4 + 52x^3 - 9x^2 - x\) $\mathrm{USp}(4)$ 0
111989.a.111989.2 111989.a \(y^2 + xy = x^5 + 5x^4 - 8x^3 - 48x^2 + x\) $\mathrm{USp}(4)$ 0
121077.a.121077.1 121077.a \(y^2 + (x^3 + 1)y = x^6 - 9x^5 + x^4 + 40x^3 - 2x^2 - 51x - 23\) $\mathrm{USp}(4)$ 0
143039.a.143039.1 143039.a \(y^2 + (x^2 + x + 1)y = -5x^6 - 34x^5 - 47x^4 + 39x^3 - 6x - 1\) $\mathrm{USp}(4)$ 0
149688.a.299376.1 149688.a \(y^2 + (x^3 + x^2)y = -x^6 + 22x^5 - 216x^4 + 636x^3 + 72x^2 + 2x\) $\mathrm{USp}(4)$ 0
150729.a.150729.1 150729.a \(y^2 + xy = -3x^6 - 3x^5 - 2x^4 + x^3 + 13x^2 + 4x - 7\) $\mathrm{USp}(4)$ 0
154541.a.154541.1 154541.a \(y^2 + (x^3 + x)y = -x^6 + 17x^5 - 101x^4 + 38x^3 + 93x^2 + 32x + 3\) $\mathrm{USp}(4)$ 0
171204.a.684816.1 171204.a \(y^2 + (x + 1)y = -3x^6 - 6x^5 + 4x^4 - 9x^3 - 29x^2 + 9x - 1\) $\mathrm{USp}(4)$ 0
187200.a.748800.1 187200.a \(y^2 + (x^3 + x)y = -x^6 + 2x^4 + 37x^2 - 156\) $G_{3,3}$ 0
190320.a.190320.1 190320.a \(y^2 + (x^3 + x)y = x^6 + 46x^4 + 576x^2 + 2379\) $G_{3,3}$ 0
194850.a.194850.1 194850.a \(y^2 + xy = 30x^6 - 39x^5 - 47x^4 + 50x^3 + 31x^2 - 17x - 9\) $\mathrm{USp}(4)$ 0
206320.a.206320.1 206320.a \(y^2 + (x^3 + x)y = x^6 - 5x^5 - 19x^4 - x^3 + 35x^2 + 4x - 17\) $\mathrm{USp}(4)$ 0
217488.a.217488.1 217488.a \(y^2 + (x + 1)y = -x^6 - 12x^5 - 30x^4 + 36x^3 - 9x^2 + x - 1\) $\mathrm{USp}(4)$ 0
220191.a.220191.1 220191.a \(y^2 + (x^3 + x)y = -x^6 + 20x^4 - 20x^3 - 123x^2 + 203x - 82\) $\mathrm{USp}(4)$ 0
225306.a.675918.1 225306.a \(y^2 + (x^3 + 1)y = -x^6 + 19x^4 + 9x^3 - 107x^2 - 162x - 65\) $\mathrm{USp}(4)$ 0
249939.a.249939.1 249939.a \(y^2 + x^2y = x^5 + x^4 - 45x^3 - 10x^2 + 541x - 357\) $\mathrm{USp}(4)$ 0
270438.a.270438.1 270438.a \(y^2 + (x^3 + 1)y = -x^6 - 4x^5 + 27x^3 + 26x^2 - 47x - 59\) $\mathrm{USp}(4)$ 0
270720.b.270720.1 270720.b \(y^2 + xy = 3x^6 + 70x^4 + 544x^2 + 1410\) $G_{3,3}$ 0
274688.a.274688.1 274688.a \(y^2 + x^2y = x^5 - 32x^4 - 80x^3 - 66x^2 - 20x - 2\) $\mathrm{USp}(4)$ 0
276083.a.276083.2 276083.a \(y^2 + (x^3 + x)y = -x^6 - x^5 + 4x^4 + 8x^3 - 16x - 25\) $\mathrm{USp}(4)$ 0
293712.a.293712.1 293712.a \(y^2 + xy = -13x^6 - 12x^5 + 63x^4 + 23x^3 - 81x^2 + 27x - 6\) $\mathrm{USp}(4)$ 0
300429.a.300429.1 300429.a \(y^2 + (x^2 + x + 1)y = -3x^6 + 26x^4 - 18x^3 - 28x^2 + 9x - 1\) $\mathrm{USp}(4)$ 0
305408.b.305408.1 305408.b \(y^2 + x^2y = x^5 + 16x^4 + 72x^3 + 17x^2 - 4x - 1\) $\mathrm{USp}(4)$ 0
323375.a.323375.1 323375.a \(y^2 + xy = -5x^6 - 5x^5 + 4x^4 - x^3 + 11x^2 + 4x - 9\) $\mathrm{USp}(4)$ 0
335104.b.335104.1 335104.b \(y^2 + x^2y = 7x^6 + 63x^4 + 189x^2 + 187\) $G_{3,3}$ 0
373030.a.746060.1 373030.a \(y^2 + x^2y = 2x^5 - 22x^4 - 51x^3 - 35x^2 - 25x - 18\) $\mathrm{USp}(4)$ 0
417152.a.417152.1 417152.a \(y^2 + (x^3 + x)y = -x^6 - 7x^5 - 15x^4 + 12x^3 + 16x^2 + x - 9\) $\mathrm{USp}(4)$ 0
434048.a.434048.1 434048.a \(y^2 + xy = -x^6 + 16x^5 - 80x^4 + 128x^3 - 64x^2 - 2x + 2\) $\mathrm{USp}(4)$ 0
438837.b.438837.1 438837.b \(y^2 + (x + 1)y = -28x^6 - 47x^5 - 43x^4 + 2x^3 + 11x^2 - 1\) $\mathrm{USp}(4)$ 0
439280.a.439280.1 439280.a \(y^2 + (x^2 + 1)y = -x^6 - 13x^4 + 36x^2 - 24\) $G_{3,3}$ 0
456960.c.913920.1 456960.c \(y^2 + xy = -5x^6 - 79x^4 - 413x^2 - 714\) $G_{3,3}$ 1
483552.a.483552.1 483552.a \(y^2 + (x + 1)y = -x^6 + 30x^5 - 278x^4 + 805x^3 - 228x^2 + 22x - 1\) $G_{3,3}$ 0
494451.a.494451.1 494451.a \(y^2 + (x^2 + 1)y = x^5 - 24x^4 - 12x^3 - 14x^2 - 6x - 1\) $\mathrm{USp}(4)$ 0
523925.a.523925.1 523925.a \(y^2 + xy = -6x^6 - 19x^5 - 29x^4 - 24x^3 - 8x^2 + 2x + 3\) $\mathrm{USp}(4)$ 0
530822.a.530822.1 530822.a \(y^2 + xy = x^5 + 9x^4 + 35x^3 - 344x - 578\) $\mathrm{USp}(4)$ 0
Next

Download all search results for